2018
DOI: 10.1155/2018/1025387
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical-Scavenging, Anti-Inflammatory, and Antibacterial Activities of Water and Ethanol Extracts Prepared from Compressional-Puffing Pretreated Mango (Mangifera indicaL.) Peels

Abstract: During the processing of mango, a huge amount of peel is generated, which is environmentally problematic. In the present study, a compressional-puffing process was adopted to pretreat the peels of various mango cultivars, and then the bioactive compounds of mango peels were extracted by water or ethanol. The phenolic compound compositions as well as the free radical-scavenging, antiinflammatory, and antibacterial activities of water extract (WE) and ethanol extract (EE) from nonpuffed (NP) and compressionalpuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…The TPC values in kernels of different mango varieties from Asia and South America have been reported at between 1571 and 29,200 mg GAE/100 g [5,17,18]; the highest TPC was observed in the ‘Chok-Anan’ cultivar from Thailand (29,200 mg GAE/100 g) [18] and ‘Ubá’ from Brazil (8254 mg GAE/100 g) [5]. Studies on the phenolic composition of mango peels have reported TPC values between 28.5 and 5724 mg GAE/100 g [5,14,15,16,17]; the highest value was observed in the ’Small Tainong’ cultivar from China [31]. In ‘Tommy Atkins’ mango, Sogi et al [6] reported TPC values in peel of between 2032 and 3185 mg GAE/100 g, and in kernel between 11,228 and 20,034 mg GAE/100 g. It is worth mentioning that previous reports on TPC in ‘sugar mango’ agroindustrial waste were not found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TPC values in kernels of different mango varieties from Asia and South America have been reported at between 1571 and 29,200 mg GAE/100 g [5,17,18]; the highest TPC was observed in the ‘Chok-Anan’ cultivar from Thailand (29,200 mg GAE/100 g) [18] and ‘Ubá’ from Brazil (8254 mg GAE/100 g) [5]. Studies on the phenolic composition of mango peels have reported TPC values between 28.5 and 5724 mg GAE/100 g [5,14,15,16,17]; the highest value was observed in the ’Small Tainong’ cultivar from China [31]. In ‘Tommy Atkins’ mango, Sogi et al [6] reported TPC values in peel of between 2032 and 3185 mg GAE/100 g, and in kernel between 11,228 and 20,034 mg GAE/100 g. It is worth mentioning that previous reports on TPC in ‘sugar mango’ agroindustrial waste were not found.…”
Section: Resultsmentioning
confidence: 99%
“…Mango agroindustrial waste contains significant amounts of high-value phytochemicals, which makes it suitable to be processed and used in food and pharmaceutical products. Mango peels are rich in phenolic compounds and carotenoids [1,5,6,14,15,16], whereas mango seed kernels are good sources of polyunsaturated fatty acids and phenolics such as ellagic acid, gallic acid, and its derivates, coumarin and mangiferin [1,5,17,18,19]. Previous studies have shown that phenolics from mango peels and kernels exhibit excellent bioactive properties against some chronic-degenerative diseases related to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorogenic acid is a common polyphenol and has been reported to have potent antioxidative and free radical-scavenging activities in vitro [11]. Chlorogenic acid also increases the resistance of LDL to lipid peroxidation and inhibits DNA damage [12]. The antioxidative and anti-inflammatory effects suggest that chlorogenic acid could aid in the prevention of cardiovascular diseases.…”
Section: Resultsmentioning
confidence: 99%
“…It is a versatile fruit used in various ways either raw or processed into juice, smoothies, sliced canned. Mango has nutraceutical properties as the leaves, roots, bark, seed and peel are used in traditional medicine to treat several ailments including piles, diarrhea, anemia, dysentery, asthma, cough, bronchitis, hypertension, toothache, leucorrhoea, hemorrhage, rheumatism [3][4][5]. Global mango production is about 51 million tons on an average harvested area of 6 million ha with an average yield…”
Section: Introductionmentioning
confidence: 99%